Trends and Rural-Urban Differences in Asthma Hospitalizations in Saskatchewan 1970-1989 - A Senthilselvan (Canadian Respiratory Journal)
OBJECTIVE: To examine the trends in hospitalization rates for atsthma in Saskatchewan from 1970 to 1989 and to investigate the differences in asthma hospitalization rates between rural and urban dwellers.